Impact of Treatment Modality on Quality of Life Among Uterine Cancer Survivors. Issue 2 (February 2023) - Yoder, A.K.; Lakomy, D.S.; Wu, J.; Andring, L.M.; Fellman, B.; Colbert, L.E.; Jhingran, A.; Klopp, A.H.; Soliman, P.; Peterson, S.K.; Lin, L.L.
Abstract: Aims: Our understanding of the impact of adjuvant therapy on longitudinal quality of life (QoL) following surgery for patients with uterine cancer is limited. The purpose of this study was to compare QoL in patients who have undergone surgery with or without radiation therapy for uterine cancer. Materials and methods: This was a cross-sectional cohort study that examined women treated for uterine cancer at MD Anderson Cancer Center from 2006 to 2017. Participants included those who underwent hysterectomy/bilateral salphingo-oophorectomy alone, with brachytherapy or external beam radiation therapy (EBRT). A non-cancer cohort of women who underwent a hysterectomy/bilateral salphingo-oophorectomy for benign indications was also identified (non-CA). To compare QoL we used the Functional Assessment of Cancer Therapy – Endometrial survey (FACT-En), a validated survey used to assess QoL. The survey has five subscales: physical, social, emotional, functional and an endometrial cancer-specific subscale. Cohorts were compared using ANOVA tests. Results: In total, 309 women responded to the questionnaire (hysterectomy/bilateral salphingo-oophorectomy 64, brachytherapy 77, EBRT 96, non-CA 72). The median time from surgery to survey completion was 6.7 years. The mean total FACT-En score for the entire cohort was 144 [standard deviation 22]. Overall QoL was different between cohorts, with the EBRT cohort reporting the lowest QoL (mean 139.4 [21.6]) and the brachytherapy cohort the highest (150.6 [18.2], P = 0.006). Among patients who had undergone cancer treatment, the EBRT cohort reported the worst endometrial-specific QoL (53.5 [8.6]), while again the brachytherapy group reported the highest score (57.5 [6.1], P = 0.007). Conclusions: QoL differences in women who have undergone different treatments for uterine cancer may persist years after treatment. In women with endometrial cancer who require adjuvant therapy, brachytherapy does not appear to have any long-term detriments on QoL. Highlights: The use of adjuvant brachytherapy after surgery for uterine cancer did not result in long-term detriments to quality of life. External beam radiation therapy after surgery for uterine cancer had impacts on physical wellbeing years after treatment. The use of chemotherapy in the definitive treatment of uterine cancer contributed to detriments in long-term quality of life.